Penerapan Konseling Kelompok dengan Teknik Cognitive Restructuring untuk Mengurangi Insecurity pada Remaja:Penelitian Tindakan Bimbingan dan Konseling - Windasantika, Windasantika; Nuraisyah, Nuraisyah; Nurjannah, Nurjannah; Putri, Amalia Rahma (CV. PUSDIKRA MITRA JAYA, 2025)
This study aims to reduce insecurity levels among adolescents through the application of group counseling using the Cognitive Restructuring technique. The research employed a Guidance and Counseling Action Research (PTBK) method across two cycles, involving six eighth-grade students from SMPN 10 Medan identified as having high levels of insecurity. The Cognitive Restructuring technique is designed to help individuals shift negative thinking patterns into more rational and adaptive ones. The results showed a decrease in the average insecurity score from 44.83 (pre-test) to 37.17 (post-test), with a significance value of 0.026 (p < 0.05), indicating a significant effect of the intervention. Normality tests and paired t-tests confirmed the effectiveness of the counseling approach. Thus, group counseling using the Cognitive Restructuring technique has been proven effective in helping adolescents overcome feelings of insecurity and improve their self-confidence.